Company law in practice (Oxford University Press, 2008)
Company Law in Practice provides a detailed overview of the salient topics in company law which the junior practitioner is most likely to encounter in the first years of practice. Such key topics covered include the constitution of companies, share and loan capital, directors' and shareholder meetings, the role and duties of directors, shareholder protection, insolvency and compulsory winding up